Immuno-pathological Study of a Deprivation Effect on the Immune Response of Post-hatched Chicks - Alrawi , Saad Thabit Jassim; Jalob, Z. Kh. (International Journal of Poultry Science, 2018)
Objective: This study was conducted to investigate the effect of deprivation during the first few days of the post-hatch period on the immune response of chicks. Materials and Methods: One hundred and twenty one days old Ross 308 birds were used and they were divided into four groups, beginning with group 1 (G1): Direct feed supply, which was divided into 2 subgroups at 11 days of age with G1.a as a positive control and G1.b as a negative control. Groups 2, 3 and 4 experienced deprivation for 24, 48 and 72 h, respectively. Results: The results showed a significant (p